Plasma p-tau181 Level Predicts Neurodegeneration and Progression to Alzheimer's Dementia: A Longitudinal Study - Wang, Yan-Li; Chen, Jinglong; Du, Zhong-Li; Weng, Haoyi; Zhang, Yuan; Li, Runzhi; Jia, Ziyan; Sun, Mengfan; Jiang, Jiwei; Wang, Fang-Ze; Xu, Jun, Alzheimer's Disease Neuroimaging Initiative (Frontiers in Neurology, 2021)
Plasma-based biomarkers would be potential biomarkers for early diagnosis of Alzheimer’s disease (AD) due to more available and cost-effective than cerebrospinal fluid (CSF) or neuroimaging. We aimed to evaluate whether phosphorylated tau181 (p-tau181) in plasma could be an accurate predictor of AD. Participants from the ADNI database included 185 cognitively unimpaired with Aβ-negative (CU-), 66 preclinical AD (CU with Aβ-positive), 164 mild cognitive impairment with Aβ-negative (MCI-), 254 prodromal AD (MCI with Aβ-positive) and 98 dementia. Multiple linear regression models, liner mixed effects models and local regression were used to explore cross-sectional and longitudinal associations of plasma p-tau181 with cognition, neuroimaging or CSF biomarkers adjusted for age, sex, education and APOE genotype. Besides, Kaplan-Meier and adjusted cox-regression model were performed to predict risk of progression to dementia. Receiver operating characteristic analyses were performed to evaluate the predictive value of p-tau181. Plasma p-tau181 level was highest in the AD dementia, followed by prodromal AD and preclinical AD. In preclinical AD, plasma p-tau181 was negatively associated with hippocampal volume (β= -0.031, p= 0.017). In prodromal AD, plasma p-tau181 was associated with decreased global cognition, executive function, memory, language and visuospatial functioning (β range -0.119 to -0.273, p< 0.05) and correlated with hippocampal volume (β= -0.028, p<0.005) and white matter hyperintensity volume (WMH) volume (β= 0.02, p=0.01). In AD dementia, increased plasma p-tau181 was associated with worse memory. In the whole group, baseline plasma p-tau181 was significantly associated with longitudinal increases in multiple neuropsychological test z-scores and correlated with AD-related CSF biomarkers and hippocampal volume (p< 0.05). Meanwhile, CU or MCI with high plasma p-tau181 carried a higher risk of progression to dementia. The area under the curve (AUC) of the adjusted model (age, sex, education, APOE and plasma p-tau181) was 0.78, additionally included CSF biomarkers was 0.84. Plasma p-tau181 level is related to multiple AD-associated cognitive domains and AD-related CSF biomarkers at the clinical stages of AD. Moreover, plasma p-tau181 level is related to the change rates of cognitive decline and hippocampal atrophy. This study confirms the utility of plasma p-tau181 as a noninvasive biomarker for early detection and prediction of AD.